Biocompatibility and osseointegration properties of a novel high strength and low modulus β- Ti10Mo6Zr4Sn3Nb alloy - Liu, Jiantao; Wang, Kao; Li, Xingyuan; Zhang, Xiwei; Gong, Xi; Zhu, Yihan; Ren, Zhiwei; Zhang, Bin; Cheng, Jun (Frontiers in Bioengineering and Biotechnology, 2023)
Ti6Al4V titanium alloy is widely used in producing orthopedic and maxillofacial implants, but drawbacks include high elastic modulus, poor osseointegration performance, and toxic elements. A new medical titanium alloy material with better comprehensive performance is urgently needed in the clinic. Ti10Mo6Zr4Sn3Nb titanium alloy (referred to as Ti-B12) is a unique medical β titanium alloy material developed by us. The mechanical properties of Ti-B12 depict that it has advantages, such as high strength, low elastic modulus, and fatigue resistance. In our study, the biocompatibility and osseointegration properties of Ti-B12 titanium alloy are further studied to provide theoretical guidance for its clinical transformation. The titanium alloy Ti-B12 displays no significant effect on MC3T3-E1 cell morphology, proliferation, or apoptosis in vitro. Neither Ti-B12 titanium alloy nor Ti6Al4V titanium alloy depicts a significant difference (P>0.05); Ti-B12 material extract injected into the abdominal cavity of mice does not cause acute systemic toxicity. The skin irritation test and intradermal irritation test reveal that Ti-B12 does not cause skin allergic reactions in rabbits. Compared to Ti6Al4V, Ti-B12 titanium alloy material has more advantages in promoting osteoblast adhesion and ALP secretion (P<0.05). Although there is no significant difference in OCN and Runx2 gene expression between the three groups on the 7th and 14th days of differentiation induction (P>0.05), the expression of Ti-B12 group is higher than that of Ti6Al4V group and blank control group. Furthermore, the rabbit in vivo test present that three months after the material is implanted in the lateral epicondyle of the rabbit femur, the Ti-B12 material fuses with the surrounding bone without connective tissue wrapping. This study confirms that the new β-titanium alloy Ti-B12 not only has low toxicity and does not cause rejection reaction but also has better osseointegration performance than the traditional titanium alloy Ti6Al4V. Therefore, Ti-B12 material is expected to be further promoted in clinical practice.